Penerapan Model Pembelajaran Discovery Learning dalam Meningkatkan Hasil Belajar Siswa - Nurrahmayani Nurrahmayani; Yusni Yusni (Journal on Education, 2024)
This research aims to describe learning outcomes through the use of the discovery learning model for Wira Mandiri Soppeng Vocational School students. This research is Classroom Action Research (PTK) with a descriptive method carried out in four stages, namely the planning stage, implementation stage, observation stage, and reflection stage. The aim of this research is whether the Discovery Learning learning model is used in Indonesian language learning. The results of this research show that the majority of students can understand the material and can complete the exercises at that time (while learning is taking place). From the results of this research it can be concluded that learning is quite effective because the majority of students can understand and accept learning well. However, to get maximum results, training needs to be increased to students.